The role of preoperative prophylactic antibiotics in hypospadias repair - Baillargeon, Emilie (Canadian Medical Association, 2014)
INTRODUCTION: We sought to determine whether the use of preoperative antibiotics is effective in reducing postoperative wound infections and urinary tract infections (UTI) in hypospadias repair. METHODS: We retrospectively reviewed all hypospadias repairs performed at the Montreal Children’s Hospital between March 2009 and September 2012. All types of primary hypospadias repairs and redo cases were included. Patients with no adequate follow-up or with missing records of antibiotics were excluded. Preoperative antibiotics were given in the form of cefazolin (50 mg/kg intravenously) when appropriate. Postoperative oral antibiotics were administered as decided by the pediatric urologist. Primary outcomes included postoperative wound infection and UTI. Secondary outcomes included the need for reoperation of hypospadias due to urethrocutaneous fistula, meatal stenosis, urethral stricture and wound dehiscence. RESULTS: In total, 157 cases of hypospadias repair were reviewed; of these 7 were excluded due to lack of follow-up. Of the remaining 150 patients, 62 received preoperative antibiotics and 88 did not. The groups were well-matched for age, hypospadias characteristics, type of repair and repair of curvature. The group that received preoperative antibiotics had a significantly higher number of stented cases (82% vs. 52% of the non-preoperative antibiotic group). Two cases of wound infection were reported (1 in the pre-operative antibiotic group and 1 in the non-preoperative antibiotic group). There was no symptomatic UTI or culture-demonstrated UTI in either group. Moreover, there was no statistically significant difference between the 2 groups in terms of primary outcomes. The complication rate was 11% (17/150 repairs) and all patients needed reoperation. This study’s important limitations include the rarity of studied end points combined with the small sample and the retrospective nature of our study. CONCLUSION: Our findings do not support the routine use of preoperative antibiotics in hypospadias repair.